2020
DOI: 10.3390/foods9020212
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cheese Yield Reduction in Manufacturing Parmigiano Reggiano from Milk with Non-Compliant Somatic Cells Count

Abstract: The mammary gland inflammation process is responsible for an increased number of somatic cells in milk, and transfers into the milk of some blood components; this causes alterations in the chemical composition and physico-chemical properties of milk. For this reason, somatic cell count (SCC) is one of the most important parameters of milk quality; therefore, European Union (EU) Regulation no 853/2004 has stated that it must not exceed the limit value of 400,000 cells/mL. The research aimed to compare chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
2
18
1
Order By: Relevance
“…Experimental yield obtained for all cheeses was lower than the findings of Rana et al (2017a) and this variation would be due to difference in milk composition and processing technique. Experimental yield is lower than the theoretical yield which might be due to loss of fat and casein in whey during cheese making resulting in low casein and/or fat retention (Franceschi et al, 2020). The higher actual yield in cheese prepared with plant protease may be attributed to the longer coagulation time (Liburdi et al, 2019) resulting in more moisture contents which increased the yield.…”
Section: Theoretical and Experimental Yieldmentioning
confidence: 90%
“…Experimental yield obtained for all cheeses was lower than the findings of Rana et al (2017a) and this variation would be due to difference in milk composition and processing technique. Experimental yield is lower than the theoretical yield which might be due to loss of fat and casein in whey during cheese making resulting in low casein and/or fat retention (Franceschi et al, 2020). The higher actual yield in cheese prepared with plant protease may be attributed to the longer coagulation time (Liburdi et al, 2019) resulting in more moisture contents which increased the yield.…”
Section: Theoretical and Experimental Yieldmentioning
confidence: 90%
“…An elevated somatic cell count in milk has an adverse effect on its chemical composition (including lower content of casein and fat and higher content of whey proteins), which negatively affects its coagulation properties, thus reducing the quantity and quality of cheese produced [31]. Franceschi et al [3] showed that the yield of Parmigiano Reggiano cheese aged for 24 months made from milk with an SSC > 400,000/mL was 9% lower than the cheese yield from milk with an SCC not exceeding 400,000/mL. A high somatic cell count in milk used for cheese production has also been linked to poorer fat retention by the curd.…”
Section: Milk Yield and Chemical Compositionmentioning
confidence: 99%
“…Global milk production is continually growing, and a large portion of it is used for cheese production. A key element of the suitability of milk for cheese production is its coagulation properties, which are associated with factors including chemical composition (content of protein, casein, fat, and minerals) [1,2] and somatic cell count [3].…”
Section: Introductionmentioning
confidence: 99%
“…The two most important hygienic parameters of milk are the somatic cells and total bacterial counts, whose increase beyond certain limits also causes worsening of the technological properties [ 5 , 6 , 7 , 8 ]. The increase of somatic cell count is associated with increase of proteolytic activity [ 9 , 10 ], which is responsible for the early degradation of casein in milk, loss of fat and protein during cheese-making [ 11 ] and consequent worsening of the cheese yield [ 9 , 12 ]. High values of bacterial count are associated with increased risk of the presence of bacterial species unsuitable for cheese-making, which cause defects in the cheese [ 13 , 14 ], with consequent depreciation of the product [ 2 , 5 ], and threaten its safety for human consumption.…”
Section: Introductionmentioning
confidence: 99%